A Closer Look at the Sleep/Wake Habits and Dark Triad Traits - Arash Rahafar; Lisa Sophie Kalbacher; Christoph Randler (Applied Sciences, 2022)
In this study, we sought to explore the association between sleep/wake habits and the Dark Triad (DT) traits. The sample consisted of 637 university students who filled out the measures of the Dark Triad, sleep quality, daytime sleepiness, and sleep timing. There was a positive relationship between the Dark Triad composite and eveningness, and a negative relationship between the DT and circadian distinctness was observed. Psychopathy appeared as the most sleep-related DT trait, and narcissism appeared as the least sleep-related one. Psychopathy and Machiavellianism predicted bedtime prior to free days stronger than the other sleep variables. This study suggests that both sleep timing and sleep stability are influenced by higher DT traits. As sleep disturbances go along with some other comorbid mental problems, looking for the possible underlying factors such as biological markers or psychological traits is warranted.